2008
DOI: 10.1038/nrmicro2029
|View full text |Cite
|
Sign up to set email alerts
|

Super-shedding and the link between human infection and livestock carriage of Escherichia coli O157

Abstract: Cattle that excrete more Escherichia coli O157 than others are known as super-shedders. Super-shedding has important consequences for the epidemiology of E. coli O157 in cattle--its main reservoir--and for the risk of human infection, particularly owing to environmental exposure. Ultimately, control measures targeted at super-shedders may prove to be highly effective. We currently have only a limited understanding of both the nature and the determinants of super-shedding. However, super-shedding has been obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
293
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(310 citation statements)
references
References 88 publications
(116 reference statements)
8
293
1
2
Order By: Relevance
“…g 21 of E. coli O157 : H7. This demonstration of high level shedding was consistent with results from cattle (Chase-Topping et al, 2008); such animals are considered important for maintaining and spreading the organism within herds (Matthews et al, 2006). There are few other reports of the concentration of this bacterium in sheep faeces, but Ogden et al (2005) found 20 of 44 E. coli O157-positive sheep shedding at 1610 3 c.f.u.…”
Section: Quantitative Studiessupporting
confidence: 75%
See 1 more Smart Citation
“…g 21 of E. coli O157 : H7. This demonstration of high level shedding was consistent with results from cattle (Chase-Topping et al, 2008); such animals are considered important for maintaining and spreading the organism within herds (Matthews et al, 2006). There are few other reports of the concentration of this bacterium in sheep faeces, but Ogden et al (2005) found 20 of 44 E. coli O157-positive sheep shedding at 1610 3 c.f.u.…”
Section: Quantitative Studiessupporting
confidence: 75%
“…In the UK, North America, Japan and much of continental Europe, such disease is commonly caused by E. coli strains of serogroup O157 (Riley et al, 1983;Kleanthous et al, 1990;Willshaw et al, 2001;Kaper et al, 2004;Chase-Topping et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Cattle and their environments are a reservoir of E. coli O157 [4][5][6]. Some strains produce verocytotoxin (verocytotoxigenic E. coli (VTEC) O157) and can be excreted in cattle faeces in high numbers, leading to the concept of super-shedding [7,8]. Certain subtypes of E. coli O157, specifically those with the genetic marker encoding toxin vtx 2, are more likely to be associated with super-shedding in cattle and these also appear to pose the greatest risk for transmission to humans [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…3 billion [4] and England approximately £750 million per annum [5]. These pathogens cause a range of symptoms from diarrhoea, abdominal pain, fever and vomiting [6][7][8][9][10][11][12] to haemolytic-uraemic syndrome (e.g. E. coli O157) [13,14], Guillian-Barre´syndrome (e.g.…”
Section: Introductionmentioning
confidence: 99%